Dimensions of cultural sustainability—Local adaptation, adaptive capacity and social resilience - Järvelä, Marja (Frontiers in Political Science, 2023)
Cultural sustainability relates to sustainable development. According to UNESCO "culture provides the necessary transformative dimension that ensures the sustainability of development processes " 1 . Originally sustainable development was defined through three dimensions, namely ecological, economic and social dimension. Further, the social dimension has been understood in multiple ways often accentuating socio-economic assets of development rather than socio-cultural capacities. Eventually, there has been an increasing interest in defining cultural sustainability as a fourth pillar of sustainable development (e.g. Sabatini 2019). The roots of this interest can be found in much earlier discussions proposing 'cultural capital' as a specific kind of capital that entails versatile resources available for building sustainable development (Throsby 1999;Throsby 2005). Moreover, the idea to include cultural sustainability as a fourth pillar of public planning for sustainable development was already proposed at the turn of the century (see Hawkes 2001).